2008
DOI: 10.1111/j.1365-313x.2008.03505.x
|View full text |Cite
|
Sign up to set email alerts
|

A tomato HD‐Zip homeobox protein, LeHB‐1, plays an important role in floral organogenesis and ripening

Abstract: SummaryEthylene is required for climacteric fruit ripening. Inhibition of ethylene biosynthesis genes, 1-aminocyclopropane-1-carboxylate (ACC) synthase and ACC oxidase, prevents or delays ripening, but it is not known how these genes are modulated during normal development. LeHB-1, a previously uncharacterized tomato homeobox protein, was shown by gel retardation assay to interact with the promoter of LeACO1, an ACC oxidase gene expressed during ripening. Inhibition of LeHB-1 mRNA accumulation in tomato fruit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
266
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(277 citation statements)
references
References 50 publications
6
266
0
5
Order By: Relevance
“…Reduced expression of these TFs in response to chilling would be expected to globally reduce many ripening-associated processes, permitting the organ to redirect metabolic resources into more suitable stress responses. In addition to these TFs, transcripts of FUL1, a RIN-interacting MADS domain protein affecting aspects of ripening, including volatile synthesis (42), as well as HB-1, a positive regulator of ethylene synthesis (43), are down during chilling. Expression of other TFs that regulate specific aspects of fruit development, including TAGL1 (44,45) and AP2a (46,47), increased during chilling.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of these TFs in response to chilling would be expected to globally reduce many ripening-associated processes, permitting the organ to redirect metabolic resources into more suitable stress responses. In addition to these TFs, transcripts of FUL1, a RIN-interacting MADS domain protein affecting aspects of ripening, including volatile synthesis (42), as well as HB-1, a positive regulator of ethylene synthesis (43), are down during chilling. Expression of other TFs that regulate specific aspects of fruit development, including TAGL1 (44,45) and AP2a (46,47), increased during chilling.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, these mutants produce drastically lower ethylene levels and fail to initiate ethylene-dependent ripening processes. Similarly, downregulation of an ACC oxidase gene (ACO) is correlated with reduced ethylene levels in the nonripening fruits of Cnr mutants and hb-1 silenced plants ( Thompson et al, 1999;Lin et al, 2008). Unexpectedly, our microarray analysis showed that there was no effect on ACS or ACO gene expression in the FUL1/2 RNAi plants.…”
Section: Ful1/2 Act Downstream or Independent Of The Ethylene Pathwaymentioning
confidence: 81%
“…In contrast, CNR 50 , Uniform (Golden-like 2) 51 and HB-1 (ref. 52) showed distinct expression patterns in hot pepper and tomato (Fig. 4).…”
Section: Comparative Fruit Ripeningmentioning
confidence: 99%